The Effectiveness of Diorama-Based Learning Media on Students’ Achievement in Islamic Cultural History: A True Experimental Study in Islamic Secondary Education - Safitri, Winda Wahyu; Susanti, Cela Petty (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the effectiveness of diorama-based learning media in improving students’ learning outcomes in Islamic Cultural History. The study addresses the challenge of low student engagement and difficulty in understanding abstract historical content by proposing a visual and experiential learning approach. This study employed a quantitative approach using a true experimental design with a pretest–posttest control group model. The population consisted of 391 seventh-grade students at MTs PPMI As-Salam Sukoharjo, Central Java, with a sample of 60 students selected through simple random sampling. The sample was divided into an experimental group and a control group, each consisting of 30 students. Data were collected using learning achievement tests and analyzed using IBM SPSS Statistics 26, including normality tests, homogeneity tests, and hypothesis testing with the Mann–Whitney U test. The results showed that the experimental group achieved significantly higher learning outcomes compared to the control group. The mean posttest score of the experimental group was 75.33, while the control group scored 43.00, with a difference of 32.33 points. Hypothesis testing revealed a significance value of 0.000 (p < 0.05), indicating a statistically significant effect of diorama-based learning media on students’ learning outcomes. This study provides empirical evidence on the effectiveness of diorama-based learning media specifically in the context of Islamic Cultural History at the madrasah tsanawiyah level using a true experimental design, which has been rarely explored in previous studies. This study contributes to the development of innovative learning media in Islamic education by demonstrating that visual and three-dimensional instructional approaches can enhance students’ understanding of abstract historical concepts. It also offers practical implications for teachers and curriculum developers in designing more engaging and effective learning environments.